Treatment of Autoimmune Bullous Diseases During Pregnancy and Lactation: A Review Focusing on Pemphigus and Pemphigoid Gestationis - Giovanni Genovese; Giovanni Genovese; Federica Derlino; Emilio Berti; Emilio Berti; Angelo Valerio Marzano; Angelo Valerio Marzano (Frontiers Media S.A., 2020)
Pregnancy may induce the onset or exacerbation of autoimmune bullous diseases such as pemphigus or pemphigoid gestationis. A shift toward T helper (Th) 2 immune response and the influence of hormonal changes have been evoked as possible triggering factors. Therapeutic management of this setting of patients may represent a challenge, mainly due to safety concerns of some immunosuppressive drugs during pregnancy and lactation. In this narrative review, we provided a comprehensive overview of the therapeutic management of autoimmune bullous diseases in pregnant and breastfeeding women, focusing on pemphigus and pemphigoid gestationis.